Investigation of K-Serotonin Structure Using Nuclear Magnetic Resonance by Quantum Chemical Methods - Yılmaz, Mücahit; Kebiroglu, Hanifi (Niyazi BULUT, 2022)
In this study, the K-Serotonin structure formed by adding potassium to Serotonin (5-HT) was investigated by quantum chemical methods. 5-hydroxytryptamine is a neurotransmitter that affects mood, making people feel happy and energetic. 5-HT and 5-HT-potassium were optimized with some base sets to find the optimal band gap using the density function theory (DFT) and Hartree-Fock (HF) method. The most suitable DFT/LanL2DZ was selected for the structure with and without additives. By calculating the values for 5-HT and K-5-HT, the effects of potassium on 5-HT binding were compared.
Keywords: Metrology; Applied and Industrial Physics; Metroloji; Uygulamalı ve Endüstriyel Fizik; Chemical Engineering; Kimya Mühendisliği